Ammonia: a review of concentration and emission models in livestock structures (2009)
Air quality in animal confinements is directly related to animal metabolisms, releasing heat, humidity and carbon dioxide (CO2) to the air from respiration and gases from digestion and feces such as NH3, CH4, H2S and dust. Heating systems produce CO and NO2 due to incomplete combustion which produces concentrations greater than those allowed by Colombian legislation (Decreto 948, 1995), and international countries such as the USA(National Organization for Security and Health NIOSH, 1994) and Brazil (NR-15, 1978), which represent some of the largest livestock development industries in the world. Among these gases, ammonia is the pollutant most often found in air inside animal confinements which deteriorates the health and productivity of animals and people. Hence, the study of ammonia has attracted the attention of researchers for years in various different countries. The objective of this work was to discover important aspects which must be taken into account in animal confinements, such as permissible ammonia concentrations. The developed models calculate concentrations and emissions, which can be used in countries such as in Colombia, where works and knowledge on environmental control and the production of gases in livestock confinements are few.